2023
DOI: 10.3390/foods12071399
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Genomic Approach for Improving Grain Protein Content in Wheat

Abstract: Grain protein content (GPC) is a key aspect of grain quality, a major determinant of the flour functional properties and grain nutritional value of bread wheat. Exploiting diverse germplasms to identify genes for improving crop performance and grain nutritional quality is needed to enhance food security. Here, we evaluated GPC in a panel of 255 Triticum aestivum L. accessions from 27 countries. GPC determined in seeds from three consecutive crop seasons varied from 8.6 to 16.4% (11.3% on average). Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 78 publications
2
4
0
Order By: Relevance
“…The observed moderate to high values of broad-sense heritability and the consistency of trait records evidenced by the significant correlations between the crop seasons suggest that a considerable part of the variation is due to inherent genetic differences among the accessions. These results agree with similar findings in bread and durum wheat for GPC [ 19 , 25 , 27 , 40 ], and TKW [ 13 , 41 ]. Given that the panel contains historical and contemporary varieties released or collected between 1925 and 2010, it is possible that the recorded genetic variance—especially for TKW—is inflated.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The observed moderate to high values of broad-sense heritability and the consistency of trait records evidenced by the significant correlations between the crop seasons suggest that a considerable part of the variation is due to inherent genetic differences among the accessions. These results agree with similar findings in bread and durum wheat for GPC [ 19 , 25 , 27 , 40 ], and TKW [ 13 , 41 ]. Given that the panel contains historical and contemporary varieties released or collected between 1925 and 2010, it is possible that the recorded genetic variance—especially for TKW—is inflated.…”
Section: Discussionsupporting
confidence: 92%
“…This study shows that a large proportion (89%) of the accessions have protein above 12%, and are suitable for preparing leavened breads [ 2 ]. The average grain protein values (13.4%) are similar to or higher than the reported information on protein contents in other bread wheat collections [ 19 , 27 , 28 , 31 , 34 ]. Additional research revealed that some accession sets had greater protein values (up to 20%), demonstrating the impact of genotype-by-environment interactions [ 22 , 23 , 33 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations